Prosedur Ideal Pengakuan bagi Anak Luar Hasil Perkawinan Siri Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 - Abdillah, Azka Aulia; Hamidah, Siti; Kawuryan, Endang Sri (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to discuss the forms of recognition of children resulting from unregistered marriages, the reasons for the need to recognize children resulting from unregistered marriages, and regulating procedures for filing recognition of children's status. The study used a normative juridical type with a conceptual approach and a statutory approach. The form of recognition for out-of-wedlock children was in the form of a notary certificate of recognition as well as a birth certificate based on the results of a DNA test (deoxyribonucleic acid). The reason for the need for legal recognition of the status of the child of unregistered marriage by his father was based on philosophical, sociological, and juridical reasons. The procedure for recognizing the status of a child was carried out by identifying the problem, checking DNA, getting married, and distributing inheritance.